Case report: Tenosynovial giant cell tumor - Fähnrich, Anke; Gasimova, Zhala; Maluje, Yamil; Ott, Fabian; Sievert, Helen; Fliedner, Stephanie; Reimer, Niklas; Künstner, Axel; Gebauer, Niklas; Kebenko, Maxim; von Bubnoff, Nikolas; Kirfel, Jutta; et al. (Frontiers in Oncology, 2024)
Tenosynovial giant cell tumor (TGCT) is a rare type of tumor that originates from the synovium of joints and tendon sheaths. It is characterized by recurring genetic abnormalities, often involving the CSF1 gene. Common symptoms include pain and swelling, which are not specific to TGCT, so MRI and a pathological biopsy are needed for an accurate diagnosis. We report the case of a 45-year-old man who experienced painful swelling in his right hip for six months. Initially, this was diagnosed as Erdheim-Chester disease. However, whole exome sequencing (WES) and RNA-Sequencing revealed a CSF1::GAPDHP64 fusion, leading to a revised diagnosis of TGCT. The patient was treated with pegylated interferon and imatinib, which resulted in stable disease after three months. Single-cell transcriptome analysis identified seven distinct cell clusters, revealing that neoplastic cells expressing CSF1 attract macrophages. Analysis of ligand-receptor interactions showed significant communication between neoplastic cells and macrophages mediated by CSF1 and CSF1R. Our findings emphasize the importance of comprehensive molecular analysis in diagnosing and treating rare malignancies like TGCT.